Orofacial pain in oncology: use of a new analgesic peptide tafalgin - G. R. Abuzarova; R. R. Sarmanaeva; G. S. Alekseeva; S. V. Kuznetsov; A. R. Gevorkov; N. A. Fedorenko; D. A. Zaretskaya (Опухоли головы и шеи, 2023)
In patients with head and neck tumors severe pain is more common than in patients with malignant neoplasms of other locations. At a third of patients, pain is the first characteristic of the disease, and after diagnosis, one half of the patients are already having pain syndrome. Аntitumor treatment often not only bring relief, but can intensify pain, which can reduce wish to treated. Part of cancer survivor continue to experience. Thus, orofacial pain syndrome should be share depending on the mechanism of appearence and tactics of treatment on three periods: pain at the stage of diagnosis, then pain syndrome in process antitumor therapy and pain in remission. It is actually if it necessary to prescribe opioid analgesics, especially for a long time. Intensity of orofacial pain syndrome is usually strong and often need to prescribe opioid analgesics. Option to opioid analgesics may be a representative of a new group of analgetics – peptide analgesics – tafalgin. The mechanism of action is due to highly selective agonism to the m1-opioid receptors. The presented clinical example demonstrates the good analgesic effect of tafalgin and the possibility use as option to analgesics of the second stage of pain management.